A New Design of Bridge-Subgrade Transition Sections Applied in Beijing-Shanghai High-Speed Railway. (2nd December 2018) - Changwei, Yang; Xinhao, Tong; Jianjing, Zhang; Haobo, Zhu
Abstract : This paper proposes a new design of bridge-subgrade transition sections in high-speed railways, in attempt to avoid typical defects observed in such sections. Field observations show that two types of defects tend to occur at bridge-subgrade transition sections of high-speed railways: ① the stiffness of the transition is usually too high so that tensile stress and even tensile cracks occur at the top surface of reserved trapezoid transition section and ② the compaction quality cannot be guaranteed within the first two meters from the abutment, which leads to excessive differential deformation within the transition section. For solving the above defects, a new design of the transition is proposed here: the section of the first 2 m from the abutment is filled with a graded gravel that is mixed with fly ash and cement to achieve specific stiffness and strength requirement, and the rest of the transition section is filled with roller-compacted concrete. For this new type of transition section, its dynamic performance is evaluated with on-site tests and numerical analysis. The results show that the bending angle of rail surface is almost constant along the route and the settlement of the rail surface along the route is in a linear distribution, which verifies the smoother transition from the rigid abutment to the flexible subgrade. Meanwhile, this new type of bridge-subgrade transition section has been successfully applied in the 680 km-long third bidding section of the Beijing-Shanghai high-speed railway, which provides valuable experiences for promoting and popularizing it in future construction of high-speed railways. In addition, the construction cost of the new type of bridge-subgrade transition section is verified by an economical efficiency analysis.